Constraints on health and health services access of rural-to-urban migrants in China: a case of Dengcun village of Beijing - Li, Yan (2010)
China is experiencing a dramatically increasing process of rural-urban migration, which is almost parallel with the phenomenal economic growth and development in China in the last decades. Given the massive scale of rural-urban migration in China, the health services access and health constraints not only matter to rural-urban migrants but also have important implications for broad public health concerns. However, this issue has not been paid enough attention in academic research.